Perspective method of cleaning water from toxic substances - Pashchenko, Bohdan; Litvinenko, Aleksandr; Shtefan, Yevgenii (My University, 2017)
The authors propose a promising method of wastewater treatment from toxic pollutants. It involves the combined decontamination from ions of heavy and non-ferrous metals in conditions of hydrodynamic cavitation. The expediency of this method is substantiated and their results are given in comparison with typical cleaning technologies.

Запропоновано перспективний метод очищення стічних вод від токсичних забруднювачів. Він передбачає комбіноване знезараження від іонів важких та кольорових металів в умовах гідродинамічної кавітації. Обґрунтовано доцільність застосування цього методу та наведено результати у порівнянні з типовими технологіями очищення.
Keywords: кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра експертизи харчових продуктів; department of foodstuff expertise; method of cleaning water; гідродинамічна кавітація; toxic substances; hydrodynamic cavitation; спосіб очищення води; токсичні речовини